Reliability of three methods for assessing shoulder strength - Hayes, K.; Walton, J.; Szomor, Z.; Murrell, G. A. (1999)
The comparable reliability of isometric strength assessment for the shoulder joint in symptomatic subjects, using manual muscle tests, a hand-held dynamometer and a spring scale dynamometer (bryantometer) has yet to be established. Similarly, the reliability of the "lift off" test for assessing subscapularis function, as first described by Gerber and Krushell (1990) has not been established. An inter-rater and an intra-rater agreement trial was undertaken to establish the reliability of five shoulder movements using the above three strength tests. In the inter-rater trial, four examiners independently measured eight symptomatic subjects using all three tests for external rotation, internal rotation, elevation and hand behind back lift off. A fifth movement of adduction was used as an internal control for the bryantometer. In the intra-rater trial, a single examiner repeated the same assessment process with nine symptomatic subjects on three different measurement occasions. Intra-class correlation coefficients (Rho) were derived by using a random effects model. Inter-ra'er agreement using the hand-held dynamometer and bryantometer for the shoulder movements tested was very good and demonstrated intra-class correlation coefficients that ranged from Rho=0.79-0.92 and Rho=0.75-0.96 respectively. Inter-rater agreement using manual muscle tests was considerably lower at Rho=0.38-0.73. Intra-rater agreement using the hand-held dynamometer, bryantometer and manual muscle tests varied from poor to perfect reliability for the shoulder movements tested (Rho= 0.79-0.96, Rho= 0.72-0.96 and Rho =0.29-1.00 respectively). Of particular note was the poor inter-rater and intra-rater reliability found for the lift off test, as assessed by manual muscle tests (Rho=0.38 and Rho=0.29 respectively). Significantly higher inter-rater reliability was demonstrated for this movement when tested with the hand-held dynamometer (p=0.002). These results indicate that acceptable levels of reliability can be obtained with the hand-held dynamometer and bryantometer for the assessment of isometric shoulder muscle function in symptomatic subjects. For investigations that use the lift off test to assess the integrity of the subscapularis muscle, the hand-held dynamometer is the measurement tool of choice.